2007
DOI: 10.1128/aem.01675-06
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Helicobacter pylori Infection Does Not Significantly Alter the Microbiota of the Murine Stomach

Abstract: We examined the impact of Helicobacter pylori infection on the murine gastric microbiota by culture and terminal-restriction fragment length polymorphism and found that neither acute nor chronic H. pylori infection substantially affected the gastric microbial composition. Interestingly, the total H. pylori burden detected by real-time PCR was significantly higher than that revealed by viable counts, suggesting that the antigenic load sustaining H. pylori-induced gastritis could be considerably higher than prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 14 publications
0
38
0
1
Order By: Relevance
“…In fact, some of the included studies did not find significant differences using cloning (14) and culture-based approaches (19,21), whereas other studies report significant changes in gastric microbiota according to H. pylori status based on DNA microarrays (17) or 454-pyrosequencing (16), which allow the study of a wider range of bacteria, thus providing a more complete view of the picture. Animal studies have also yielded contradicting findings, as H. pylori infection altered significantly the constitution of gastric microbiota in a BALB/c mice model (27) and in Mongolian gerbils (28), but it does not significantly alter the murine gastric microbiota (29).…”
Section: Discussionmentioning
confidence: 89%
“…In fact, some of the included studies did not find significant differences using cloning (14) and culture-based approaches (19,21), whereas other studies report significant changes in gastric microbiota according to H. pylori status based on DNA microarrays (17) or 454-pyrosequencing (16), which allow the study of a wider range of bacteria, thus providing a more complete view of the picture. Animal studies have also yielded contradicting findings, as H. pylori infection altered significantly the constitution of gastric microbiota in a BALB/c mice model (27) and in Mongolian gerbils (28), but it does not significantly alter the murine gastric microbiota (29).…”
Section: Discussionmentioning
confidence: 89%
“…In wild type mice, culture-independent studies found that neither long nor short-term H. pylori infection had a substantial impact on the gastric microbiota. 18,19 Studies in hypergastrinemic INS-GAS mice demonstrated that H. pylori infection caused a reduction in Bacteroidetes and an increase in Firmicutes. 20 When these mice were gnotobiotically colonized with members of the altered Schaedler's flora (ASF), H. pylori infection was accompanied by decreased Bacteroides, and both a decrease (Clostridium) and increase (Lactobacillus) in Firmicutes.…”
Section: Does H Pylori Infection Impact the Gastric Microbiota?mentioning
confidence: 99%
“…The gastric environment altered by H. pylori could be mimicking that of the lower gastrointestinal tract, allowing these bacteria to flourish. However, Tan et al (2007) reported gastric microbiota did not change after 6 months in C57BL/6 mice infected with H. pylori (strain SS1) and was dominated by Lactobacillus reuteri and Lactobacillus murinus. One explanation could be that this strain of helicobacter does not induce extensive inflammation, which may also play a role in altering the gastric milieu and subsequent bacterial colonization.…”
mentioning
confidence: 99%